EVALUASI DAYA SIMPAN DAGING DARI SAPI BALI YANG DIGEMBALAKAN DI AREA TPA DESA PEDUNGAN, DENPASAR SELATAN - I W. G. A., Samudra; Ariana, I N. T.; Lindawati, S. A. (Jurnal Peternakan Tropika, 2016)
The purposes of this research were to determine the microbial profile and storability of beef which cattle grazing at landfill area (T 1 ). The object of this research was bali cattle that looked after at TPA Pedungan Village, South Denpasar. This research was carried out for 2 months, in Wayan Sija’s traditional abatoar located at Banjar Bersih, Darmasaba Village and microbiology test in Product Technology and Microbiology, Faculty of Animal Science, Udayana University. This research used a Completely Randomized Design (CRD) by two treatments with six repitations. The results of the research showed that microbial profile TPC unsignificant difference (P>0.05), Coliform and E.coli bacteria showed a significant difference (P<0.05) between T 1 and T 0 . Observations storability at 0 hour showed unsignificant results (P>0.05), but observations next 2 hours, 4 hours, 6 hours, 8 hours and 10 hours showed a significant difference (P<0.05) , Conclusions of this research showed that the microbial profile TPC between T i and T 0 is higher but still at the threshold of food safety, while Coliform and E.coli between T 0 and T 1 is same contamine of patoghen microbial. Storability of T 1 is only 10 hours while T 0 is12 hours.
Keywords: Coliform, E. coli,Storability, TPC